Cyberbullying on YouTube social media: Ria Ricis's feedback on haters - Diyanti Diyanti; Vyki Mazaya (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2022)
Interactive communication in virtual space enables free and uncontrolled communication. This study aims to know the communication of Ria Ricis and the netizen and her feedback on haters. Ria Ricis is an influencer who often gets a negative response the netizen on her social media contents. This study will look at Ria Ricis feedback communication patterns on YouTube with Wilbur Schramm's theory. The data source was based on the haters' comments on a video